Introductory Management Science / Fourth Edition - Eppen G.D; Gould F.J; Schmidt C.P (Prentice Hall, 1993)
Preface, Introduction: Models and Modelling, Deterministic Models, Linear Programming: Formal and Spreadsheet Models, Linear Programming: Geometric Representations and Graphical Solutions, Analysis of LP Models: The Graphical Approach, Linear Programming: The Simplex Method, Linear Programming: Special Applications, Integer and Quadratic Programming, Network Models, Inventory Control with Known Demand, Heuristics and Multiple Objectives and Goal Programming, Calculus Based Optimization and an Introduction to Nonlinear Programming, Probabilistic Models, Simulation, Decision Theory and Decision Trees, Project Management: PERT and CPM, Inventory Models with Probabilistic Demand, Queuing Models, Forecacting, Appendices, Index.
Preface, Introduction: Models and Modelling, Deterministic Models, Linear Programming: Formal and Spreadsheet Models, Linear Programming: Geometric Representations and Graphical Solutions, Analysis of LP Models: The Graphical Approach, Linear Programming: The Simplex Method, Linear Programming: Special Applications, Integer and Quadratic Programming, Network Models, Inventory Control with Known Demand, Heuristics and Multiple Objectives and Goal Programming, Calculus Based Optimization and an Introduction to Nonlinear Programming, Probabilistic Models, Simulation, Decision Theory and Decision Trees, Project Management: PERT and CPM, Inventory Models with Probabilistic Demand, Queuing Models, Forecacting, Appendices, Index.